Hubungan Dukungan Sosial dan Harga Diri Terhadap Kesejahteraan Psikologis Mahasiswa FKIP - Cindy Asli Pravesti; Anisah Nur Firdaus (Jurnal Muria Research Guidance and Counseling (MRGC), 2026)
Students' psychological well-being is a central concern in higher education, as it shapes academic performance and overall quality of life. Social support, self-esteem, and psychological well-being serve as the central variables explored in this study, with students from the Faculty of Teacher Training and Education at Universitas PGRI Adi Buana Surabaya as the research population. A quantitative correlational design was adopted, with 303 active students recruited through purposive sampling. Data were gathered using Likert-scale instruments and analysed via Spearman's rho correlation, selected after all variables failed the Kolmogorov–Smirnov normality test (p < .05). Findings revealed that social support is positively and significantly associated with psychological well-being (r = .489, p < .05), while self-esteem showed an even stronger positive association (r = .690, p < .05). Moreover, social support correlated meaningfully with self-esteem (r = .606, p < .05). These results indicate that internal resources specifically self-esteem play a more decisive role than external resources in predicting student well-being. Practically, the study recommends that university counselling programmes integrate both self-esteem enhancement initiatives and social network strengthening to foster optimal psychological health.